Holocene reef evolution in a macrotidal setting: Buccaneer Archipelago, Kimberley Bioregion, Northwest Australia - Solihuddin, Tubagus; O'Leary, Mick; Blakeway, David; Parnum, Iain; Kordi, M.; Collins, L. (Springer Verlag, 2016)
This study uses information derived from cores to describe the Holocene accretion history of coral reefs in the macrotidal (up to 11 m tidal range) Buccaneer Archipelago of the southern Kimberley coast, Western Australia. The internal architecture of all cored reefs is broadly similar, constituting well-preserved detrital coral fragments, predominantly branching Acropora, in a poorly sorted sandy mud matrix. However, once the reefs reach sea level, they diverge into two types: low intertidal reefs that maintain their detrital character and develop relatively narrow, horizontal or gently sloping reef flats at approximately mean low water spring, and high intertidal reefs that develop broad coralline algal-dominated reef flats at elevations between mean low water neap and mean high water neap. The high intertidal reefs develop where strong, ebb-dominated, tidal asymmetry retains seawater over the low tide and allows continued accretion. Both reef types are ultimately constrained by sea level but differ in elevation by 3–4 m.